Basis Set Effects on the Stabilities and Interaction Energies of Small Amide Molecules Adsorbed on Kaolinite Surface - Najwa-Alyani Mohd Nabil; Lee Sin Ang; Shukri Sulaiman (Universitas Gadjah Mada, 2023)
Adsorptions of small amide molecules, acetamide (AA) and N-methyl-acetamide (NMA) on the surface of kaolinite are investigated in this study. The focus is on the basis set effects towards the stabilities and the interaction energies of the molecules on the Al–O surface. With a fixed B3LYP functional, we increased the size of the basis sets for the single-point calculations, to find the converged interaction energies and obtain the relative stabilities. We found that, under the direct usage of Pople-type and Dunning’s correlation consistent basis sets, it is not possible to achieve the pattern of convergence for the interaction energies and the relative stabilities. Compared to the complete basis set (CBS) extrapolation scheme, the double zeta basis sets deviated the most, in the range of 21 to 27%, while it is from 1 to 7% for the triple zeta basis sets. Based on the results, we suggest using 6-311++G(2df,2pd) or cc-pVQZ for energy-related quantities. Compared to AA, NMA attached more strongly by 0.5 eV on the surface of Al–O.